We Choose What to Fear in Indonesian Horror Cinema - Achmad Ridwan Noer (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M) Institut Bisnis dan Komunikasi LSPR, 2021)
Horror movies in Indonesian cinemas have seen a recent surge of viewers despite being associated with exploiting sensualism under the blanket of horror. Meanwhile, the top ten viewed Indonesian horror movies in recent years managed to somewhat acquire the trust of Indonesians to come back to watch more horror movies in their favourite cinemas. This paper employs the qualitative content analysis method to better grasp what movie trailer elements are employed by the top 10 viewed Indonesian horror movies and see what are the similarities and differences in the elements of horror they present. Ultimately, as the market demands it, a natural selection for the kinds of horrors Indonesians watch is currently on going.